Pengaruh Terpaan Media Sosial Tiktok terhadap Minat Berkebun pada Followers @mini_garden12 - Puspitasari, Bella; Mariyono, Joko; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Social media exposure is a condition in which individuals are exposed to information from social media such as Tiktok and can influence individual behavior including the formation of gardening interest. Gardening interest is a feeling of liking or being interested in doing gardening activities. This study aims to describe and analyze the effect of Tiktok social media exposure on gardening interest in @mini_garden12 followers. The research was conducted from October to December 2024 with the Tiktok account @mini_garden12 as the research location. The research method used is a survey with a quantitative approach. The research sample was determined by purposive sampling and taken by quota sampling with a total of 161 respondents. Data collection was carried out by distributing questionnaires and documentation. The data obtained were analyzed descriptively and quantitatively using multiple linear regression tests. The results showed that the level of media exposure, namely duration, frequency, and attention, was categorized as very high and the level of interest in gardening was categorized as high. The independent variables of duration, frequency, and attention with the control variables of age, gender, education, residence, and type of smartphone operating system simultaneously affect interest in gardening. The variables of frequency, attention, and residence have a partial effect on interest in gardening while the variables of duration, age, gender, education, residence, and type of smartphone operating system have no partial effect. The independent variables and control variables influence the interest in gardening on Tiktok @mini_garden12 followers by 59.8% which is classified as quite strong and the rest is influenced by other variables.